2018
DOI: 10.3391/ai.2018.13.2.09
|View full text |Cite
|
Sign up to set email alerts
|

Forecasting impact of existing and emerging invasive gobiids under temperature change using comparative functional responses

Abstract: In this study, we have performed a large-scale assessment on the native distribution range of the marine non-indigenous species (NIS) found in at least one of the European Seas (Mediterranean, NE Atlantic Ocean, Black, Baltic Sea). As a basis, we have used the most updated pan-European NIS inventory, provided by the European Alien Species Information Network. All taxonomic groups have been considered for this analysis, taking into account established NIS in European Seas (824 taxa in total). The vast majority … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 7 publications
(13 citation statements)
references
References 9 publications
(13 reference statements)
0
11
1
Order By: Relevance
“…Although the impact of Proterorhinus semilunaris has had little attention (Kocovsky et al 2011) compared with that of Neogobius melanostomus (Kornis et al 2012), Gebauer et al (2018) showed similar per capita impact of the species at 20°C. In predatory fish species, type II FR (i.e., inverse density-dependent predation) is a common foraging pattern, although variations in environment may produce shifts in FR types (Koski and Johnson 2002).…”
Section: Discussionmentioning
confidence: 98%
See 3 more Smart Citations
“…Although the impact of Proterorhinus semilunaris has had little attention (Kocovsky et al 2011) compared with that of Neogobius melanostomus (Kornis et al 2012), Gebauer et al (2018) showed similar per capita impact of the species at 20°C. In predatory fish species, type II FR (i.e., inverse density-dependent predation) is a common foraging pattern, although variations in environment may produce shifts in FR types (Koski and Johnson 2002).…”
Section: Discussionmentioning
confidence: 98%
“…Similarly, Dubs and Corkum (1996) observed higher FR of Neogobius melanostomus compared with native mottled sculpin (Cottus bairdii). In a comparison of Neogobius melanostomus with Proterorhinus semilunaris, Gebauer et al (2018) found similar per capita ecological impact of both species towards pelagic prey. Both Neogobius melanostomus and Proterorhinus semilunaris are opportunistic feeders with diets consisting chiefly of benthic invertebrates, while their consumption of fish eggs and juveniles is generally low (French and Jude 2001;Vašek et al 2014).…”
Section: Introductionmentioning
confidence: 84%
See 2 more Smart Citations
“…The relationships between consumer resource uptake and resource densities result in three FR types : linear Type I, hyperbolic Type II, and sigmoidal Type III (Holling, ; Jeschke et al., ). Functional responses have been applied to various aspects of ecology (Abrams, ; Englund & Harms, ; Faria, Godoy, & Trinca, ; Feldman, ), such as assessing adaptive behaviours (Abrams, ) and how resource abundance influences the per capita effects of individual predators under a number of environmental variables such as temperature (Stephens & Krebs, ), but only more recently have comparative FR analyses been used to assess invasive species impacts on resources such as prey, whereby the impact of an invader is contrasted with functionally similar native and/or non‐native species (Dick et al., ; Gebauer, Veselý, Kouba, Buřič, & Drozd, ; Xu et al., ).…”
Section: Introductionmentioning
confidence: 99%